Analysis of Pre-service Science Teachers Critical Thinking Abilities : A Valuable Insights for Designing Instructional Strategies - Verawati, Ni Nyoman Sri Putu; Rokhmat, Joni; Harjono, Ahmad; Makhrus, Muh; Sukarso, AA (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to analyze the critical thinking abilities of pre-service science teachers, specifically focusing on students majoring in physics. Recognizing the pivotal role of critical thinking in science education, this research investigates the key abilities of analysis, inference, evaluation, and decision-making within the context of routine science learning activities. The study employs a descriptive research design, utilizing quantitative observational methods. A critical thinking ability test, comprising eight items, was administered to 19 pre-service science teachers. The validity and reliability of the test instrument were rigorously assessed through empirical testing and Cronbach's alpha, confirming the instrument's suitability for measuring the intended abilities. Descriptive and inferential statistical analyses, including ANOVA, were conducted to evaluate the critical thinking abilities of the participants. The results indicate an overall low level of critical thinking across all indicators, with no significant differences identified among the abilities of analysis, inference, evaluation, and decision-making. The descriptive analysis revealed that the students generally fell into the "Not Critical" category, reflecting significant deficiencies in their ability to engage deeply with scientific content. The ANOVA results further supported these findings, showing a lack of significant variation in critical thinking abilities, which points to a systemic issue within the current educational practices. These findings have important implications for science education, underscoring the need for comprehensive instructional strategies that address all aspects of critical thinking.